Improving Students’ Speaking Ability through Audiolingual Method in Producing Asking, Giving, and Refusing Expressions at Junior High School - Irwansyah Jurmasari; Masoud Rahimi Domakani; Amin Ali Mubarak (Journal of Language, Literature, and Educational Research, 2026)
Purpose of the study: This study aimed to determine whether the implementation of the Audiolingual Method could improve the speaking skill of first-year students at Junior High School State 26 Makassar, particularly in producing asking, giving, and refusing expressions in English conversations. Methodology: This study used Collaborative Classroom Action Research (CAR) based on Kemmis and McTaggart’s model with two cycles consisting of planning, action, observation, and reflection. The subjects were 23 students of SMP Negeri 26 Makassar. Instruments included speaking tests, observation checklists, lesson plans, students’ worksheets, and scoring rubrics adapted from Heaton (1988) covering accuracy, fluency, and comprehensibility. Main Findings: The findings showed significant improvement in students’ speaking skills after applying the Audiolingual Method. The mean score increased from 2.2 in the pre-test to 3.8 in Cycle I and 4.4 in Cycle II. Students also showed better classroom participation, confidence, cooperation, pronunciation, fluency, and comprehensibility during speaking activities. Novelty/Originality of this study: This study highlights the effectiveness of the Audiolingual Method through systematic drilling and repetition activities to improve junior high school students’ speaking performance. Unlike previous studies focusing on pictures or questioning techniques, this research emphasizes oral habit formation, pronunciation practice, and communicative confidence using structured dialogue repetition in classroom action research.